Variability of the height of plants of hybrid forms of spring common wheat (Triticum aestivum L.) under different ecological and geographical conditions - E. I. Ripberger; N. A. Bome; D. Trautz (Вавиловский журнал генетики и селекции)
The results of two-year research (2013–2014) of the variability of plant height in spring common wheat hybrid forms (F4, F5) in three geographical localities, including Russia (Tyumen region) and Germany (Baden-Württemberg and Lower Saxony), which differ considerably in soil and climatic conditions, are presented. These three localities also differ in temperature and availability of water during the growing seasons of spring wheat. Differences between the geographical points in water supply and aridity during two growing seasons (2013–2014) were assessed on the basis of G.T. Selyaninov’s hydrothermal coefficient (HTS). The height of plants of different hybrids showed different responses to differences in environmental factors. Hybrids demonstrated a moderate degree of height variability (CV = 11–25 %). Hybrid forms characterized by the largest range in plant height within a locality were identified. The morphotypes of the hybrids were presented by undersized and moderately sized plants. It was found that hybrids formed higher plants under conditions of sufficient moisture. The contributions of the major factors (point, year, a genotype) to the formation of the height of plants were investigated by three-way analysis of variance. The results of this analysis demonstrated that the environmental conditions were responsible for the largest proportion of the explained variation of the variable under study (plant height). Two hybrid forms ( Hybrid × Lutescens 70 and Cara × Skent 3) with the least expressed variation in plant height and the highest lodging resistance were identified. Height of plants is considered one of the indicators characterizing the environmental plasticity of genotypes under different soil and climatic conditions.